Antimicrobial Resistance Pattern of Shigella species Over Five Years at a Tertiary-care Teaching Hospital in North India (Journal of Health, Population and Nutrition, 2011)
DOI: http://dx.doi.org/10.3329/jhpn.v29i3.7878J HEALTH POPUL NUTR 2011 Jun;29(3):292-295